DAMPAK KENAIKAN TARIF DASAR LISTRIK PADA USAHA LAUNDRY DI KECAMATAN SAIL KOTA PEKANBARU - Taufik Hendrianto; Azwar Harap; Rahmita Budiartiningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research entitled Impact Analysis of Basic Electricity Tariff Increase On Laundry Business In Sail District Pekanbaru City. The purpose of this study is to determine and analyze the impact of basic electricity tariff increase on laundry business in Kecamatan Sail Pekanbaru City. This research was conducted in Sail District with sample number 36 laundry business. Data collected in this research are primary data and secondary data. Primary data obtained through direct interview with business actors, while secondary data obtained from government agencies such as BPS and sub-district office. The analytical tool used in this research is different test analysis. Result of conclusion obtained in this research is increase of TDL increase laundry business cost, but give impact of increasing amount of laundry demand because society also experience increase of TDL so cost to do washing and clothes iron more or less equal to using laundry service and society prefer to use service laundry rather than do it yourself.Keywords : Revenue, Basic electricity tariff